2021
DOI: 10.1002/cphc.202000884
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Nanostructure Dynamics on Au(111) with Adsorbed Sulfur due to Au−S Complex Formation

Abstract: Chemisorbed species can enhance the fluxional dynamics of nanostructured metal surfaces which has implications for applications such as catalysis. Scanning tunneling microscopy studies at room temperature reveal that the presence of adsorbed sulfur (S) greatly enhances the decay rate of 2D Au islands in the vicinity of extended step edges on Au(111). This enhancement is already significant at S coverages, θS, of a few hundredths of a monolayer (ML), and is most pronounced for 0.1–0.3 ML where the decay rate is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…In probing gas/surface interactions, surface-sensitive probes such as X-ray photoelectron spectroscopy (XPS) have been, for some time, a critical tool for understanding heterogeneous catalysis reaction mechanisms and for optimizing catalyst activity and selectivity. The corresponding studies at the electrolyte/solid interface are, however, a still-developing area of research. With respect to vanadium oxynitrides, recent ex situ photoemission studies on vanadium nitride nanoparticles have shown that vanadium oxynitrides formed in situ are the active species and that an N surface state with an N 1s binding energy of 396.5 eV is associated with NRR activity. Moreover, the relative photoemission intensity of this feature correlated with the NRR activity of the nanoparticle .…”
Section: Introductionmentioning
confidence: 99%
“…In probing gas/surface interactions, surface-sensitive probes such as X-ray photoelectron spectroscopy (XPS) have been, for some time, a critical tool for understanding heterogeneous catalysis reaction mechanisms and for optimizing catalyst activity and selectivity. The corresponding studies at the electrolyte/solid interface are, however, a still-developing area of research. With respect to vanadium oxynitrides, recent ex situ photoemission studies on vanadium nitride nanoparticles have shown that vanadium oxynitrides formed in situ are the active species and that an N surface state with an N 1s binding energy of 396.5 eV is associated with NRR activity. Moreover, the relative photoemission intensity of this feature correlated with the NRR activity of the nanoparticle .…”
Section: Introductionmentioning
confidence: 99%